EVALUACIÓN FINANCIERA PARA LA CREACIÓN DE UN BAR PUB IRLANDÉS “SHORT SHORT’S” EN LA CIUDADELA LOS MOLINOS DE LA CIUDAD DE LOJA - Carrión Vásquez, Mayra Alejandra (2018)
The "Financial Evaluation for the creation of an Irish Pub " Short Short's” in the citadel Los Molinos from the Loja city" thesis research, was developed based on the previously objectives raised in the project. Firstly, proceeded to determine the population and show an essential step to establish the demand and supply and thus apply the surveys, which helped to know the degree of acceptance of 94%. With the data obtained it was possible to determine the viability of the project in relation to the physical, technological and engineering aspects and operation, determining that the best alternative for the location of the bar would be on the corner of the streets 18 de Noviembre and Zapotillo of the citadel Los Molinos from the Loja city, and the anual installed capacity of 20,966 people. The second objective was carried out with the quotation of the different costs and expenses necessary for the bar´s creation, values that served to realize the different budgets that determined the cost of the product to offer, the same one that gave a value of $6,07 for both beverages and snacks, considering a profit margin of 60%. With the preparation of financial statements, it is expected to obtain a profit of $41.422,54 for the first year. In the third objective, the initial investment for the implementation of the proposal was determined, yielding a value of $27.107,88, an amount that will be financed in the following manner; $19.302,14 with own capital and the difference, that is, $7,805.74, through a loan granted by Banco del Pacífico at an interest rate of 15% per year for a term of 5 years. The capital recovery time corresponds to 3 months, 25 days. For the fourth objective, the different financial evaluation criteria were applied with a projection of 5 years, obtaining the following results: a VAN 5 of $ 248.424,62; a TIR of 305% that exceeds the expected TMAR of 9%, the benefit-cost ratio reflects that for every dollar invested there is $2,36 of profit; the avarage accounting return of 211% is higher than the average accounting rate of return of %. Finally, the indicator of sensitivity due to its different increases in costs indicates being sensitive, and in the decreases in income the project is the same, therefore, it is profitable. Consequently, the feasibility of the proposal has been demonstrated and the commencement of the corresponding activities is recommended.